2021
DOI: 10.1111/apm.13185
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of skin microbiota in shoulder surgery infections

Abstract: Post-surgical infections arise due to various contributing factors. Most important is the presence of potential pathogenic microorganisms in the skin complemented by the patient´s health status. Cutibacterium acnes is commonly present in the pilosebaceous glands and hair follicle funnels in human skin. After surgical intervention, these highly prevalent, slow-growing bacteria can be found in the deeper tissues and in proximity of implants. C. acnes is frequently implicated in post-surgical infections, often re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 104 publications
(139 reference statements)
0
6
0
Order By: Relevance
“…Cutibacterium acnes is a common human skin bacterium with proposed bene cial roles for human health. However, recent ndings suggest that it is also a frequent cause of OIAIs associated with shoulder arthroplasties [24,25]. Some studies have found evidence for polymicrobial OIAIs involving C. acnes, but also monomicrobial OIAIs with multiple C. acnes strains belonging to different phylotypes (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Cutibacterium acnes is a common human skin bacterium with proposed bene cial roles for human health. However, recent ndings suggest that it is also a frequent cause of OIAIs associated with shoulder arthroplasties [24,25]. Some studies have found evidence for polymicrobial OIAIs involving C. acnes, but also monomicrobial OIAIs with multiple C. acnes strains belonging to different phylotypes (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…at bay [46]. C. acnes ’ dominance within hair follicles further influences on the risk of postoperational infections as they are not eradicated by normal pre‐operational preparations [47] (Table 1).…”
Section: Healthy Human Skin Microbiotamentioning
confidence: 99%
“…The inner volume of the terminal hair follicle is thereby 10 times that of vellus hair follicle. Corresponding to the higher prevalence of terminal hair follicles, men have an increased risk of deep tissue postoperational infections [47]. Considerable bacterial aggregates are found within hair follicles in particular in moist and sebaceous skin habitats [45,49,51] and, accordingly, serve as potential reservoir of the skin microbiota [30,54].…”
Section: Microbial Distribution and Growth Condition In Healthy Skinmentioning
confidence: 99%
“…Biofilms are recalcitrant toward the immune system and antimicrobials [ 11 ] due to a combination of factors such as the protective matrix covering the aggregates [ 12 , 13 ], the size of the aggregates [ 14 , 15 ], the metabolically inactive state of the bacteria [ 16 , 17 ], and their differentiation into distinct phenotypes inside the aggregates [ 14 , 18 , 19 ]. Studies have shown that skin surface aggregates can persist even after surgical preparation and disinfection of the skin [ 20 , 21 ] and that the average diameter of aggregates on the skin surface is 5–15 μm in diameter, whereas aggregates located in hair follicles are larger with an average size of 50 μm in diameter [ 9 ].…”
Section: Introductionmentioning
confidence: 99%